2009
DOI: 10.1007/s10544-009-9294-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel 3-D model for cell culture and tissue engineering

Abstract: A novel method of making microcapsules in a macrocapsule is demonstrated as a 3-D culture system in this article. Mouse embryonic stem (mES) cells as model cells were used in the 3-D culture space, and the cell viability and histological observation were conducted. Furthermore, Oct4 gene expression was evaluated for the undifferentiated status of mES cells in this 3-D model. The results showed that mES cells can grow in this 3-D model and retain their normal viability and morphology. This 3-D model allows mES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Beyond differences in mass transport kinetics, studies have also indicated that culturing cell in 3-D matrix instead of 2-D surfaces lead to alteration in cell phenotypes and function, including differentiation 21, 22 , proliferation 23 and survival 24 . For example, many tumor cells display reduced chemosensitivity in 3-D cultures 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Beyond differences in mass transport kinetics, studies have also indicated that culturing cell in 3-D matrix instead of 2-D surfaces lead to alteration in cell phenotypes and function, including differentiation 21, 22 , proliferation 23 and survival 24 . For example, many tumor cells display reduced chemosensitivity in 3-D cultures 25 .…”
Section: Resultsmentioning
confidence: 99%
“…After 16 days of cultivation in static dish, the physiological density of live cells was found only within the top 128 mm of construct thickness. A tissue fabricated from suspended cells in microcapsules for cell-based drug delivery and tumor models shows its critical size (approximately 200 -300 mm) [22]. In these methods, oxygen concentration and cell viability decrease with the distance from the construct surface.…”
Section: Discussionmentioning
confidence: 99%
“…Factors used for stem cell differentiation include signals from blood vessels such as vascular endothelial growth factor A (VEGF-A) and fetal soluble factors, which play an important role in the pancreatic differentiation of embryonic stem cells. [46][47][48][49][50] Additionally, undifferentiated embryonic stem cells are genetically engineered with b cell genes such as Nkx6.1 to obtain insulin-secreting cells. …”
Section: Embryonic Stem Cellsmentioning
confidence: 99%